The effect of preoperative apple juice on the prevalence of hypoglycaemia in paediatric patients - Lee, Clover-Ann (My University, 2013)
Background: Children have historically been fasted for prolonged periods preoperatively to reduce the volume and acidity of their gastric contents and thus the risk of regurgitation and pulmonary aspiration. Evidence shows that this risk is not increased by following the current recommended fasting guidelines, and that prolonged fasting may be detrimental to children, who may present with hunger, thirst, depleted intravascular volume, metabolic acidosis and hypoglycaemia. A recent study at Charlotte Maxeke Johannesburg Academic Hospital showed a 18.5% prevalence of biochemical hypoglycaemia, defined as a blood glucose concentration of less than 3.5 mmol/l, in children from one to five years of age presenting for elective surgery. Aims: The aims of this study were to document the prevalence of biochemical hypoglycaemia in children from the ages of one to five years who were given apple juice to drink at least two hours preoperatively, and to compare these results to a historical control group. Methods: A prospective, contextual comparative study design was used. Approval was obtained from the University of the Witwatersrandʼs Human Ethics Committee and other relevant authorities. The groups were matched for age and weight. Consent was obtained from the guardians of all children who met the inclusion criteria before being enrolled in the study. A standard 200 ml carton of commercially available apple juice was offered to each participant. The volume and time of the juice consumed was documented, along with relevant demographic data. Inhalational induction of anaesthesia proceeded a minimum of two hours later, and a venous glucose concentration was measured. Results: The prevalence of biochemical hypoglycaemia was statistically significantly reduced in the intervention group (p = 0.0163), eliminating the effect of prolonged preoperative fasting. Conclusion: The consumption of clear apple juice on the morning of surgery is a safe, inexpensive, effective way to reduce the prevalence of hypoglycaemia in children presenting for elective surgery.
Keywords: Preoperative Care; Body Fluids; Surgery; Hypoglycemia